The effect of coarsening of primary austenite on the ultimate tensile strength of hypoeutectic compacted graphite Fe-C-Si alloys. (15th July 2019) - Hernando, Juan Carlos; Elfsberg, Jessica; Ghassemali, Ehsan; Dahle, Arne K.; Diószegi, Attila
Abstract: The effect of primary austenite morphology on the ultimate tensile strength (UTS) of hypoeutectic compacted graphite Fe-C-Si alloys (CGI) is studied by isothermal coarsening experiments. Secondary dendrite arm spacing (SDAS) and the morphological characteristics related to the surface area of primary austenite, Mγ and DID Hyd, increase with the cube root of coarsening time. UTS decreases linearly with increasing coarseness of primary austenite. The eutectic and eutectoid microstructures are unaffected by the primary austenite morphology. These observations demonstrate the strong influence of primary austenite morphology on the mechanical properties of hypoeutectic CGI alloys. Graphical abstract: Unlabelled Image